PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN KEWIRAUSAHAAN UNTUK MEMANFAATKAN SUMBER DAYA PERIKANAN DI DESA KAPUR KABUPATEN KUBU RAYA - Fita Kurniasari; Koriyantika Koriyantika (Universitas Muhammadiyah Pontianak, 2018)
The abundance of freshwater fish farming in Desa Kapur is one of the potential resources of the villages. However, there are still problems with the processing of aquaculture products in Desa Kapur, namely the lack of knowledge of the community in utilizing the results of the cultivation. As a result, many farmers only sell live fish at uncompetitive prices. In addition, there is a need for society to have knowledge to market their products outside the Kapur Village. Therefore, it is necessary to cultivate aquaculture products to improve economic growth and a better entrepreneurial spirit. Thus it is expected to help improving the economy of the community and entrepreneurial spirit in Desa Kapur.